Using JITT in a database course - Martínez Porras, Alexandra (2012)
This paper describes our experience using Just-in-Time Teaching (JiTT) in a graduate Software Testing course during two semesters. JiTT is a pedagogical strategy that bridges in-class and out-of-class components through preparatory web-based assignments, known as warm-ups. Our JiTT design was as follows. The preparatory out-of-class component consisted of a reading test, which required students to read a chapter from the textbook and then answer a web-based test available in our virtual platform. Reading tests were due the day before class in order to give the teacher enough time to read over the student's responses and adjust the next lesson accordingly. The in-class component was organized around student common misconceptions or difficulties, extracted from the reading tests submitted by the students. Discussions and cooperative learning activities were among the teaching strategies used in class. Our approach was assessed from the students' and teacher's perspective. The students' perspective was obtained from a survey. The teacher's perspective consisted in an assessment of strengths and limitations. Results from our evaluation show that a vast majority of students believe their learning improves when they prepare for class by reading the material in advance. They also think that reading tests are an effective way of verifying that students did the assigned reading. Most of them also consider that JiTT is an appropriate teaching strategy for the course. From the teacher's perspective, a major strength found was that students were more engaged in class, asking interesting questions that enriched class discussion. Also, the use of open-ended (essay-type) questions in reading tests has the additional benefit of helping them become better writers (organize their ideas better and clarify their thinking through writing).